Stability and thermal conductivity of multi-walled carbon nanotube nanofluid - Rashidi, Saba (2018)
Heat transfer has a critical role in industrial applications such as home appliances, pharmaceuticals, chemical process industries and metal working. Nanofluid is utilized as an excellent heat transfer medium for a massive range of applications owing to the outstanding thermal properties of nanoparticles. It is kind of new engineering material involving particles with nanometer-sized that is dispersed in base fluid. Thermal conductivity of nanofluid has much more effective than pure fluid. it is much vital for further use in practical applications to know more about stability and thermal characteristics of such a nanofluid. The current conventional heat transfer fluids limit the heat transfer advancement due to high vapor pressure and low thermal stability. Dispersion of Multiwalled Carbon Nanotubes (MWCNT) in conventional base fluids increased the heat transfer rate but do not overcome the issue with the vapor pressure and thermal stability of base fluids. Thus, (PVA + water) and (XG + water) are proposed as the new base fluids dispersed with CNT to overcome the limitation of the conventional heat transfer fluids. In this research, Multiwalled Carbon Nanotubes (MWCNT) is dispersed in base fluid. Though owing to the hydrophobic nature of the surface, nanoparticles tend to agglomerate and they are leading to sedimentation, thus its properties cannot be fully used. The aim of this study is to investigate the effect of Polyvinyl Alcohol (PVA) and Xanthan Gum (XG) as stabilizers on stability, thermos-physical and rheological properties of CNT nanofluids. Therefore, PVA and XG were added separately to overcome this limitation in which they acted as potential dispersants. Experimental work containing of stability studies under the effects of CNT concentration (0.01-0.1 wt. %), XG concentration (0.04-0.2 wt. %), PVA concentration (0.25-3 wt. %) and sonication time (4 hrs.), respectively have been carried out. By using the UV-Vis spectrophotometer and thru visual observation, the stability of CNT nanofluids was investigated. Thermophysical properties as a function of temperature (25-70°C) and concentration of CNT nanofluids such as viscosity, thermal conductivity and density were measured. Density of the CNT nanofluids enhanced slightly with enhancing CNT concentration and also the density of nanofluid reduced with enhancing temperature. The enhancement in density can examine insignificantly. The PVA and XG surfactant with CNT nanofluids are further characterized for specific heat capacity utilizing the differential scanning calorimetry (DSC) and the thermal degradation temperature utilizing the thermogravimetric analysis (TGA) separately. Specific heat capacity measurements illustrate that the specific heat capacity of the CNT nanofluids with surfactants (PVA and XG) increase with increase in CNT concentration owing to the high surface energy of the nanoparticles arising from the high surface area per unit volume or per unit mass of the nanoparticles. By using an optical microscope and AFM, the dispersion state of the CNT-water nanofluid and also the effective length of MWCNTs of the actual suspension is further examined, respectively. PH, FTIR and RAMAN study of the nanofluid suspensions have also been measured. The CNT nanofluid was found to be more stable in pH range between 5-5.6 for PVA and for 5.9-6.18 XG. Nanofluids are found to be stable at 4.0 hrs. sonication times, the optimum XG and PVA concentration was found to be between 0.04-0.2 wt. % and 0.5-1.5 wt. % for the range of the CNT concentration studied. Zeta potential test showed that the nanofluids were capable to remain stable for at least 3 months. Thermal conductivity was observed to be strongly dependent on temperature and CNT concentration. Furthermore, it was found that the thermal conductivity increment of CNT-water nanofluid enhanced non-linearly with temperature and there was approximately 1 to 44 % (PVA) and (XG) 1.8 to 14.30 % increment for the range of CNT concentration and temperature studied. Additional, viscosity was also found to be a function of CNT, XG and PVA concentration. CNT nanofluids with surfactants (PVA and XG) have higher viscosity which enhanced with CNT concentration and constant shear rate (1000 s-1) but reduced with enhancing temperature. In the presence of XG/PVA and CNT, no significant change in viscosity was observed. In the last part of this research, the experimental results of thermal conductivity of XGCNT and PVA-CNT nanofluids are compared with Hamilton and Crosser and Xue models. In summary, CNT nanofluids are found to be more suitable for heat transfer applications in many industries owing to their increased thermal conductivity property. This work provides abundant information on the behaviour of CNT nanofluids. Introducing suitable support for surfactants with nanoparticles during particle formation, agglomeration of particles is drastically reduced, allowing the heat transfer process to proceed effectively. A thermal conductivity was increased at very low particle loading and exceeding the predictions of various published models on nanofluids.